The impact of user decision-making in the application of computational compartment fire models. (July 2017) - Baker, Greg; Spearpoint, Michael; Frank, Kevin; Wade, Colleen; Sazegara, Shahriar
Abstract: This paper describes a programme of blind modelling and benchmarking experiments that was part of a larger collaborative research project. The modelling and subsequent experiments were performed for a compartment representing a typical lounge in a residential occupancy with a number of different combustible items located in pre-defined positions, and a specific ignition source. The modellers were provided with information such as the compartment dimensions and number/size of ventilation openings, the location and nature of the combustible items, and the details of the ignition source. The objective for the blind modelling was to predict both the ignition times for each of the secondary items, as well as the heat release rate for the compartment. As input for the blind modelling, each modeller had to select a range of different input data that included a heat release rate curve and ignition properties for each combustible item. A series of three identical experiments were then carried out and the blind modelling predictions were compared to the experimental results. The specific focus of this paper is to describe what choices the different modellers made when selecting the different input data for the blind modelling exercise. The impact that this decision-making had on the predictions, and hence comparison with the subsequent experimental data, is discussed. The input data varied considerably between the different modellers, and this had a significant impact on the modelling predictions and the comparison with the experimental results. The user decision-making in this blind modelling and experimental benchmarking programme provides an illustration of one of the many aspects of the significant subjectivity that is likely to occur in everyday performance-based fire safety engineering (PBFSE). A comprehensive performance-based design will involve a number of performance objectives. The modelling and experimental programme presented in this paper deals with only one aspect of a life safety performance objective. Notwithstanding this limitation, any subjectivity of the type illustrated in this paper has the potential to create uncertainty as to the actual level of safety that will be achieved, a lack of confidence in the eyes of an official who may be reviewing/approving a design, and hence provide a barrier to the effective implementation of PBFSE.